2015
DOI: 10.1523/jneurosci.1956-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Chemotherapeutic Paclitaxel Increases Human and Rodent Sensory Neuron Responses to TRPV1 by Activation of TLR4

Abstract: Peripheral neuropathy is dose limiting in paclitaxel cancer chemotherapy and can result in both acute pain during treatment and chronic persistent pain in cancer survivors. The hypothesis tested was that paclitaxel produces these adverse effects at least in part by sensitizing transient receptor potential vanilloid subtype 1 (TRPV1) through Toll-like receptor 4 (TLR4) signaling. The data show that paclitaxelinduced behavioral hypersensitivity is prevented and reversed by spinal administration of a TRPV1 antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
244
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(261 citation statements)
references
References 74 publications
16
244
1
Order By: Relevance
“…LPS is expressed on the outer membrane of gram negative bacteria, including the inactivated Mycobacterium tuberculosis present in complete Freund’s adjuvant used in our in vivo inflammation studies. LPS is an exogenous ligand for the TLR4 receptor, which is expressed in sensory neurons (Diogenes et al, 2011, Li et al, 2014, Li et al, 2015) and exposure to LPS enhances the expression of TNFα, IL-1β, COX-2 and MCP-1 in sensory neurons (Tse et al, 2014, Miller et al, 2015), thus recapitulating the activation of multiple pathways elicited by inflammation. Furthermore, LPS acutely enhances the sensitivity of sensory neurons as demonstrated by nociceptive behaviors following injection into the hindpaw of rodents (Ferreira et al, 1993, Calil et al, 2014) and by in vitro experiments, where LPS enhances the excitability and exocytotic activity of sensory neurons (Hou and Wang, 2001, Diogenes et al, 2011, Meseguer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…LPS is expressed on the outer membrane of gram negative bacteria, including the inactivated Mycobacterium tuberculosis present in complete Freund’s adjuvant used in our in vivo inflammation studies. LPS is an exogenous ligand for the TLR4 receptor, which is expressed in sensory neurons (Diogenes et al, 2011, Li et al, 2014, Li et al, 2015) and exposure to LPS enhances the expression of TNFα, IL-1β, COX-2 and MCP-1 in sensory neurons (Tse et al, 2014, Miller et al, 2015), thus recapitulating the activation of multiple pathways elicited by inflammation. Furthermore, LPS acutely enhances the sensitivity of sensory neurons as demonstrated by nociceptive behaviors following injection into the hindpaw of rodents (Ferreira et al, 1993, Calil et al, 2014) and by in vitro experiments, where LPS enhances the excitability and exocytotic activity of sensory neurons (Hou and Wang, 2001, Diogenes et al, 2011, Meseguer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear which endogenous mediators are involved in paclitaxel-dependent activation or sensitization of TRP channels, as paclitaxel cannot directly activate TRP channels (4,5,8). Interestingly, paclitaxel is an inducer of some Cytochrome-P 450 epoxygenases (e.g., CYP2C8, CYP2C9) (9).…”
mentioning
confidence: 99%
“…chemotherapy-induced neuropathy | neuropathic pain | TRPV1 | telmisartan | oxidized lipids R ecent studies identified members of the transient receptor potential-family of ion channels (TRPV1, TRPA1, and TRPV4) as contributors to both mechanical and cold allodynia during oxaliplatin and paclitaxel-induced neuropathy (1)(2)(3)(4)(5). Activation or sensitization of TRPV1 and TRPA1 can lead to enhanced release of CGRP and substance P, both of which can cause neurogenic inflammation and recruitment of T cells (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This nociceptor activation requires Lipid A, the membrane anchored moiety of LPS [3]. LPS may also signal through a Toll-like receptor (TLR4) mediated sensitization of the capsaicin receptor TRPV1 [4,8,11]. …”
Section: Bacterial Pathogensmentioning
confidence: 99%